International Adjudication, Rhetoric and Storytelling. (21st April 2017) - Bianchi, Andrea
ABSTRACT: Legal professionals involved in dispute settlement might greatly benefit from taking a look at literature and learning more about storytelling and rhetoric. These techniques can provide legal arguments with enhanced persuasive force. Unlike in literature, storytelling in law is almost exclusively used as a way of structuring legal arguments, of making them more convincing in order to persuade whatever audience the speaker may address. Likewise, rhetorical techniques can help procure the audience's adherence to the speaker's argumentation. A judgment (like any other piece of legal writing) will always aim at persuading the audience to which it is addressed. For any court or tribunal, it is a matter of authority, credibility and prestige. The more persuasive the judgment is, the more the authority of the judicial organ will be reinforced, and its credibility and prestige enhanced.